2020
DOI: 10.1002/jsfa.10904
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and protective effect of guava (Psidium guajavaL.) leaf extract on piglet intestines

Abstract: BACKGROUND Dietary intervention is an important approach to improve intestinal function of weaned piglets. Phytogenic and herbal products have received increasing attention as in‐feed antibiotic alternatives. This study investigated the chemical composition of guava leaf extract (GE) by ultrahigh‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS). Meanwhile, we investigated the effects of dietary supplementation with GE on diarrhea in relation to immune responses and intestinal health in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…In our previous study, the diarrhea incidences of piglets in the BC, NC, S50, S100, and S200 were 1.79, 21.43, 14.29, 8.93, and 7.14%, respectively. It suggested that dietary addition of GE could reduce diarrhea incidence significantly in weaned piglets challenged by ETEC ( 17 ). In general, diarrhea disease caused by ETEC infections is a major risk factor for impaired intestinal structure and barrier function of piglets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, the diarrhea incidences of piglets in the BC, NC, S50, S100, and S200 were 1.79, 21.43, 14.29, 8.93, and 7.14%, respectively. It suggested that dietary addition of GE could reduce diarrhea incidence significantly in weaned piglets challenged by ETEC ( 17 ). In general, diarrhea disease caused by ETEC infections is a major risk factor for impaired intestinal structure and barrier function of piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies also suggested that GE was rich in phenolics ( 28 ), and phenolics have a positive effect on gut health ( 29 ). Specifically, quercetin and myricetin, known as the main phenolic constituents in GE ( 17 , 30 ), have been demonstrated to enhance intestinal barrier function ( 31 ). Consequently, it is assumed that the abundant phenolics in GE exerted anti-inflammatory ( 32 ) and anti-diarrhea activity ( 15 ), and improved the intestinal barrier function and gut mucosal integrity of piglets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During weaning, piglets are exposed to and must quickly adapt to various psychological, environmental, and physiological stressors ( 1 ), all of which are associated with weaning-related stress, which leads to changes in intestinal structure and function as well as imbalances in intestinal microbiota ( 3 ), eventually leading to post-weaning stress diarrhea. At present, dietary intervention is the most common method to alleviate weaning stress diarrhea ( 4 , 5 ), and plant extracts can improve the growth performance, antioxidant capacity, and immunity of livestock and poultry to prevent various diseases ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%